EP.FRI.477 Neutrophil-To-Lymphocyte Ratio (NLR) as a Predictor of Acute Appendicitis. (28th October 2021) - Tasleem, Sadia; Gulnaz, Nadia
Abstract: : The most common reason for an acute surgical assessment of the abdomen is acute appendicitis with a rate as high as 30 %There is a lifetime risk of 8.6% and 6.7% in men and women respectively. The common age for presentation is between that of 5 and 4.4 while 28 is the median age. The objective of this study was to determine the diagnostic accuracy of (NLR) neutrophil-to-lymphocyte ratio to prognosticate severe/ complicated appendicitis by taking histopathology of the appendix as a gold standard. Methodology: This cross-sectional validation study was conducted at the department of surgery and western vascular institute, University College Hospital Galway, Ireland retrospectively for a period of 6 months in 2016 And approximately 186 cases with appendicitis were enrolled in the study. Results: The mean age of patients in this study was 29.15±9.54 years, the ratio of male to female was 1:1.7. The sensitivity, Specificity was 97.1% and 25.2% respectively and the diagnostic accuracy of NLR was 38.7% taking histopathology as the gold standard. We observed that the sensitivity, specificity, and diagnostic accuracy of NLR changes with the duration of symptoms in days, the sensitivity, specificity, and diagnostic accuracy of NLR was 100%, 17.0%, and 28.7% respectively for <3days and 92.3%, 93.75% and93.1% respectively for >3 days. Conclusion: According to our study results the (NLR) neutrophil-to-lymphocyte ratio is a highly sensitive tool to predict severe/ complicated appendicitis by taking histopathology as the gold standard, but with the low value of diagnostic accuracy in terms of specificity.